The development of the international human rights protection system at the regional level (African Union example) (International relations and international law Journal, 2017)
In the article the author explores the human rights protection system, functioning at the regional level in the framework of the African Union. As an example, consider individual landmark case in the practice of the African Commission on Human and Peoples’, which had a positive impact in the protection of human rights in the region. The authors conclude that, within the jurisdiction of this institution formulates its own principles and norms of human rights, accumulated the necessary experience of cooperation between Member States, within its membership and, in general, is a region-wide process of advocacy development, but all the same needs to be improved.
Keywords: Africa; the African Union; the African Charter; colonialism; human rights